Republic of Madagascar - Joint World Bank-IMF Debt Sustainability Analysis - World Bank (World Bank, Washington, DC, 2019)
Madagascar is assessed at low risk of external debt distress. This marks a change from moderate risk in the June 2018 DSA, despite a broader definition of external debt, and reflects an upgrade in Madagascar’s debt carrying capacity rather than a change in the debt path. Under the baseline, external public and publicly guaranteed (PPG) debt is well below applicable thresholds. Stress tests do not breach the threshold applicable to countries with medium debt-carrying capacity. Total (external plus domestic) PPG debt is below the benchmark under the baseline, but growth shocks drive the present value of the ratio of debt to GDP above the benchmark. Shocks could also introduce liquidity problems, as the debt-service to revenue ratio could exceed 100 percent over the long term. The overall rating, of moderate debt distress, remains consistent with the 2018 DSA. These assessments continue to be supportive of Madagascar’s current plans to scale up its borrowing to meet its investment needs, though other factors are also critical.